PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN PADA KEDAI CAPPUCINO MIX KEBAB JENDRAL CISAUK TANGERANG - Faujiah; Rosa Lesmana (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of service quality and price on customer loyalty at the Cappucino Mix Kebab Jendral Cisauk Tangerang, both partially and simultaneously. The method used is a quantitative method with a descriptive approach. The sampling used is non-probability sampling, a purposive sampling type with the Slovin formula. While to obtain data, questionnaires were distributed to 100 respondents. The results of the study showed that service quality had a significant effect on customer loyalty partially, as evidenced by the regression equation Y = 4.793 + 0.876 X1, a correlation coefficient of 0.918, meaning that the two variables have a very strong relationship. The determination value is 84.3%. Hypothesis testing obtained a calculated t value> t table or (22.903> 1.984) and was strengthened by a significance value (0.000 <0.05). Price has a significant effect on customer loyalty partially proven by the results of the regression equation Y = 1.910 + 0.934 X2, the correlation coefficient of 0.935 means that the two variables have a very strong relationship. The determination value is 87.4%. Hypothesis testing obtained a calculated t value> t table or (26.023> 1.984) and is strengthened by a significance value (0.000 <0.05). The results of the study of service quality and price simultaneously have a significant effect on purchasing decisions proven by the results of the regression equation Y = 1.109 + 0.391 X1 + 0.568 X2. The correlation coefficient value between the independent variable and the dependent variable is obtained at 0.953, meaning that it has a very strong relationship. The simultaneous determination coefficient value is 90.7%. Hypothesis testing simultaneously obtained a calculated F value> F table or (474.828> 2.700) and is strengthened by a significance value (0.000 <0.05). Thus H0 is rejected H3 is accepted. Thus H0 is rejected H3 is accepted. This means that there is a significant influence simultaneously between service quality and price on customer loyalty.